Pengaruh GPM, NPM, dan DER Terhadap Harga Saham pada PT. Aneka Tambang Tbk pada Tahun 2014 - 2021 - Devi Permata Sari Bangun; Graciela Novelia; Lisa Anggraeni (Yayasan Literasi Sains Indonesia, 2022)
This study aims to determine the effect of Gross Profit Margin (GPM), Net Profit Margin (NPM), Debt To Equity Ratio (DER) on stock prices at PT Aneka Tambang Tbk for the 2014-2021 period. The method used is a descriptive analysis study with a quantitative approach. Data analysis used includes the classical assumption test, T test, F test, determination test, and correlation coefficient test. The results of the study show that the Gross Profit Margin has no effect on the stock price at PT Aneka Tambang Tbk for the 2014-2021 period as evidenced by the significance value of the Gross Profit Margin variable of 0.343 or greater than 0.05. Net Profit Margin has no effect on the stock price of PT Aneka Tambang Tbk for the 2014-2021 period as evidenced by the significance value of the Net Profit Margin variable of 0.513 or greater than 0.05. The Debt To Equity Ratio has no effect on the share price of PT Aneka Tambang Tbk for the 2014-2021 period as evidenced by the significance value of the variable debt to equity ratio of 0.349 or greater than 0.05.